HOXA10 induces BCL2 expression, inhibits apoptosis, and promotes cell proliferation in gastric cancer - Song, Chenlong (Cancer Med, 2019)
Homeobox A10 (HOXA10) has been implicated critical for the promotion of carcinogenesis, but the underlying mechanism between HOXA10 and malignant gastric cancer (GC) phenotype remains elusive. In the present study, we analyzed and validated that HOXA10 and BCL2 expressions were elevated both at the mRNA and protein levels in GC tissues. Upregulated HOXA10 promoted GC cell proliferation with reduced apoptosis in vitro and accelerated GC tumor growth in vivo. Bioinformatics analysis and quantitative real‐time polymerase chain reaction (qRT‐PCR) experiment inferred that HOXA10 might upregulate the expression of BCL2. By performing western blot, chromatin immunoprecipitation and quantitative PCR (ChIP‐qPCR), and rescue experiment, we found that HOXA10 might bind to BCL2 promoter region, induce its expression, and thus inhibit intrinsic apoptosis pathway. Moreover, higher expression of HOXA10 and BCL2 predicted poor overall survival (OS) in GC patients. In summary, our study indicated that HOXA10 was upregulated in GC, and that HOXA10 might promote cell proliferation by elevating BCL2 expression and inhibiting apoptosis.